Facial Nerve Trauma: Clinical Evaluation and Management Strategies. Issue 5 (May 2019) - Brown, Stav; Isaacson, Brandon; Kutz, Walter; Barnett, Samuel; Rozen, Shai M.
Abstract : Summary: The field of facial paralysis requires the reconstructive surgeon to apply a wide spectrum of reconstructive and aesthetic principles, using a comprehensive array of surgical tools, including microsurgery, peripheral nerve surgery, and aesthetic facial surgery on the road to optimize patient outcomes. The distinct deficits created by different anatomical levels of facial nerve injury require a fundamental understanding of facial nerve anatomy. Palsy duration, followed by location and mechanism, will determine mimetic muscle salvageability, by means of either direct repair, grafting, or nerve transfers, whereas longer palsy durations will necessitate introducing a new neuromuscular unit, whether by muscle transfer or free functional muscle transplant. A thorough history, physical examination, and basic understanding of ancillary studies, emphasizing palsy duration, location, and mechanism of injury, are critical in evaluation, prognostication, and treatment strategies in traumatic facial palsy patients. The importance of ancillary and aesthetic procedures cannot be overstated. Although these do not provide motion, they constitute essential tools in the treatment of facial paralysis, providing both protective and improved aesthetic outcomes, yielding the highest impact in final surgeon and patient satisfaction, bringing our patients to smile not only on the outside, but also on the inside. Abstract : Supplemental Digital Content is available in the text.